The role of the epithelial Na+ channel (ENaC) in high AVP but low aldosterone states - Stockand, James D. (Frontiers in Physiology, 2012)
Due to the abundance of seminal discoveries establishing a strong causal relation between changes in aldosterone signaling, the activity of the epithelial Na+ channel (ENaC) and blood pressure, the role of ENaC in health and disease is understood almost exclusively through the concept that this channel functions (in the distal nephron) as a key end-effector controlling renal sodium excretion during feedback regulation of blood pressure by the renin-angiotensin-aldosterone system (RAAS). Recent findings of aldosterone-independent stimulation of ENaC by vasopressin challenge the completeness of dogmatic understanding where ENaC serves solely as an end-effector of the RAAS important for control of sodium balance. Rather the consequences of activating ENaC in the distal nephron appear to depend on whether the channel is activated in the absence (by aldosterone) or presence (by AVP) of simultaneous activation of aquaporin 2 water channels. Thus, a unifying paradigm has ENaC at the junction of two signaling systems that sometimes must compete: one controlling and responding to changes in sodium balance, perceived as mean arterial pressure, and the other water balance, perceived as plasma osmolality.